Symptoms Of Premenstrual Syndrome That Affect The Performance Of Female Martial Arts Athletes In Nganjuk Regency - Prinata, Prena; Waluyo, Kiaonarni Ongko; Christiany, Irine; Wuryaningsih, Sri Hardi (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Premenstrual syndrome or PMS is a collection of physical and psychological symptoms that occur during the luteal phase of the menstrual cycle that has an impact on the productivity of female athletes so that there is an assumption that women often become weak during the menstrual period. This study aims to analyze the symptoms of premenstrual syndrome with performance among female martial arts athletes in Nganjuk Regency. This research uses an analytical method. The sample of this study used the purposive sampling technique of 80 athletes. The variables in this study were the symptoms of premenstrual syndrome and athlete performance. The location and time of this research is the Nganjuk Regency Martial Arts Pavilion on March 1-31, 2025. Data collection was carried out by questionnaire. The results obtained from premenstrual symptoms of female martial arts athletes in Nganjuk Regency were mostly experiencing severe premenstrual symptoms. The performance of female martial artists in Nganjuk Regency mostly has sufficient performance. The influence of premenstrual symptoms on the performance of female martial arts athletes in Nganjuk Regency showed a significant influence. It is hoped that female martial arts athletes pay more attention to a balanced nutritional pattern during PMS, including increasing the intake of iron, magnesium, and vitamin B6 to help reduce physical and emotional symptoms, it is recommended to maintain hydration, monitor the menstrual cycle regularly, and adjust the intensity of exercise according to the body condition during PMS.